Capabilities and limitations of the Jicamarca radar as an MST radar - Woodman Pollitt, Ronald Francisco (1983)
The Jicamarca antenna is the largest radar antenna in the world. It is a flat and almost horizontal array of cross-dipoles, covering an area of 300 m by 300 m (9 Ha). It has a center frequency of 50 MHz with a bnndwidth of 1 MHz (determined by power combiners and splitters at the feed point of the antenna).